Project Delivery Method Selection Criteria for Building Projects in Surabaya, Indonesia - Andi Andi; Stephanus Eduard Sugianto; Yosep Setiadi Lukas (Civil Engineering Dimension, 2024)
Selecting an appropriate Project Delivery Method (PDM) is a crucial decision for owners that significantly influences the success of a construction project. Various criteria, such as the nature of construction projects and the specific characteristics of owners and projects, should be properly considered to make this decision. This paper first assesses and evaluates the key criteria for selecting a PDM for building projects in Surabaya. It then proposes a multi-criteria decision-making model for the selection of three PDMs, namely Single General Contractor, Multiple Primes, and Design and Build. A three-step questionnaire survey was conducted to achieve the objectives. The initial analysis revealed six important selection criteria, which were then modelled and used in the subsequent survey. Using the Analytical Hierarchy Process (AHP) procedures, the second analysis determined the weights of each criterion for the three PDMs. The paper discusses these weights, suggesting the relative strengths of each PDM. Finally, the paper tests the robustness of the model using three building projects in Surabaya.